Causes of construction delay: a case study in Libya - Fackroon, Ellafi H.; Kadir Pakir, Abdul Hamid; Omran, Abdelnaser (2008)
Delays on construction projects are a universal phenomenon. And it is probable that most construction projects will incur some sort of a delay before they are completed. Even though various studies have been considered into the causes affecting delays, these studies seldom discuss common and general causes of delays in construction projects. Thus, comprehensive study on these delays is essential. Since the problems are rather contextual, the study needs to focus on specific causes of delaying like insufficient coordination and ineffective communication between involved parties in construction projects located at Benghazi City in Libya. Literature review and a questionnaire survey targeted at construction projects in the Libya’s country and have been used as the tools to carry out this study. This paper presents the findings of a survey aimed for identifying some of the most important causes of delays in construction projects in the above mentioned city. It is hoped that these findings will guide efforts to enhance the performance of the construction Industry. This paper also explores and provides some guidelines and actionable information which can be led to enhance the construction process.